Aplicação de técnicas avançadas de ressonância magnética nuclear para análise de produtos farmacêuticos com foco em análise de misturas - Paez, Elida Betania Ariza (Universidade Federal de São Carlos, 2024)
In this work, the Designed Refocused Excitation and optional Mixing for Targets In vivo and Mixture Elucidation (DREAMTIME) technique was applied for the analysis of complex degradation mixtures of pharmaceutical compounds, focusing on cases with spectral overlapping and low intensity signals in 1H-NMR spectra. The DREAMTIME technique improves molecular specificity compared to conventional spectra by combining double selective excitation with amplitude- and phase-modulated waveforms. The use of spectral filters allows to cancel unwanted components, isolating one or more compounds simultaneously within a mixture. The study had two main objectives: (1) the implementation of the DREAMTIME sequence using a standard sample of known composition and concentration, and (2) its application in the selection and separation of degradation products of the drugs sofosbuvir (SOF) and tenofovir disoproxil fumarate (TDF), under acidic and basic conditions, without the need for physical separation. The degradation products were identified by two-dimensional NMR techniques, such as COSY, TOCSY, HMBC and HSQC, and the signals were selectively isolated using DREAMTIME. In the case of SOF, seven acidic degradation products and four basic degradation products were identified. For TDF, four products were identified in the acidic degradation and five in the basic degradation. The DREAMTIME technique proved to be effective in recovering the signals of the compounds, resolving the spectral overlap between the parent drug and the degradation products. Quantification was performed based on quantitative 1H-NMR spectra, after 48 hours of degradation. The degradation of SOF as an active principle was determined under acidic conditions (10.10%), due to the presence of isolated signals. However, the absence of isolated signals under basic conditions for SOF and under both conditions for TDF prevented the accurate determination of the degradation of these compounds. It is important to highlight that the optimization of the DREAMTIME technique parameters, such as the pulse time, the average coupling constant in J, and the mixing time filter, was essential to improve the selectivity and intensity of the signals, ensuring the obtaining of clean and well-resolved spectra.
Application of advanced nuclear magnetic resonance techniques for analysis of pharmaceutical products with a focus on mixture analysis
Keywords: RMN; DREAMTIME; Produtos de degradação; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA